MPS 11-09 Renal Afferent Peptidergic Neurons in the Control of the Autonomous Nervous System – What are Primary Stimuli?. (September 2016) - Ditting, Tilmann; Rodionova, Kristina; Heinlein, Sonja; Hilgers, Karl Friedrich; Ott, Christian; Schmieder, Roland; Amann, Kerstin; Veelken, Roland
Abstract : Objective: Renal afferent nerve fibers comprise a complicated neuro-paracrine regulatory system influencing the autonomous nervous system. We tested the hypothesis that the activity of renal afferent neuronal units is mainly altered by inflammation in cardiovascualr disease and hypertension. Design and Method: As inflammatory model, normotensive renal inflammation (RI) was induced by i.v. injection of 1.75 mg/kg BW OX-7 antibody to rats, hypertension by unilateral clipping of one renal artery (2k1cl model) in rats 3 weeks prior to experiments. Retrograde labelling (DiI) identified renal afferent neurons among dorsal root ganglion (DRG) neurons (Th11-L2). Patch clamp recordings characterized neurons as highly active or "tonic", i.e. sustained action potential (AP) firing versus low active or "phasic", i.e. <5 APs according to their firing response to current injections. Electrophysiological parameters were determined in all neurons investigated, proteinuria and renal morphology assessed for all kidneys. Results: In nephritis, the number of neurons with a tonic response pattern decreased significantly (43, 4% vs. 64, 8%, p < 0.05) as compared to controls. Interestingly. in renovascular hypertension (2k 1cl model, n = 92) only neurons with projections to the clipped kidney showed a significant decrease in tonic firing pattern 30.6% [23/75], whereas the non-clipped kidney showed an unaffected amount of tonically firing units (67.5% [50/74], p < 0.05). There was no increase in blood pressure (BP) in RI animals. RI rats exhibited albuminuria (61 ± 6 μg/24 h), interstitial infiltration of macrophages (26 ± 4 cells/high-power field) and glomeruli (3.7 ± 0.6 cells/glomerular cross-section) suggesting active renal inflammation. In contrast, in 2K 1cl animals BP was increased to 180/100 mmHg, but no signs of renal inflammation occurred. Conclusions: Contrasting our hypothesis neither inflammation (nor high blood pressure) may be primarily responsible for the decreased activity pattern of afferent renal neuron in our experiments. Rather decreased perfusion occurring in a clipped kidney with renal stenosis and likely also present in nephritis might be important.